Macrocyclic polyamines : synthesis and applications - Yu, Xiaoqi; Zhang, Ji (Of Sichuan da xue) (Wiley-VCH, 2018)
Macrocyclic polyamines are a class of widely-used important compounds. This is the first book that systematically summarizes the synthesis and applications of macrocyclic polyamines and their analogues, including the properties and synthetic methods of macrocyclic polyamines, chemical nucleases based on macrocyclic polyamines, the derivatives of macrocyclic polyamines as nano-vector materials, macrocyclic polyamines derivatives for bio-imaging, chemical sensors based on macrocyclic polyamines, and other applications of macrocyclic polyamines. This book will not only provide a reference for the researchers working on macrocyclic polyamines, but also offer opportunities for researchers in related research fields to understand the benefits of these key compounds.